Transforming Good Governance Challenges in the Extractive Industries into Opportunities to Instigate Local Community Development in Sub- Saharan Africa: A Case Study of Cameroon (African Journal of Law and Politics, 2023)
The concept of good governance looms as a defining issue in 21st Century Natural Resources Law because of the need to improve transparency and accountability in the extractive industries, notably the mining sector. A broad consensus voice that, natural resources remain the hallmark for unprecedented growth and sustainable development in resources-rich Sub-Saharan African countries for they add lump revenues into the government’s treasury in the form of taxes and royalties. Yet, the co evolution between natural resource exploitation and local community development is gloomy. As natural resources are being exploited, the status quo in communities hosting extractive sectors is stunted growth, impoverishment and by extension, ignite conflicts—a situation tagged: “Resource Curse”. This article sets out to unveil the poor governance plaguing Cameroon’s mining industry and the opacity condoned by the lawmaker. Our opinion holds that, poor governance is the root cause of underdevelopment in local communities endowed with abundant natural resources. A succinct analysis of primary and secondary sources of data, and an empirical research based on data collection will be adopted. This article recommends a clear, detailed and efficient law in relation to good governance in Cameroon’s mining industry.